Czech Defense Policy in the Light of Strategic Culture - Vladimír Karaffa; Cyril Svoboda (Vojenské rozhledy)
The article analyzes key aspects of the development of the Czech Republic's defense policy since 1989, with a focus on the role of strategic culture. It examines historical, political, and social factors that have shaped the Czech Republic's approach to defense and security issues. Special attention is given to the transformation of the Czech Armed Forces, the transition to a professional military model, and responses to changing geopolitical threats. The analysis also considers public perceptions of the military, the influence of historical narratives on strategic culture, and the attitudes of political elites toward defense matters. The article highlights the importance of strategic culture as an analytical framework for understanding long-term trends and the evolution of defense policy, while suggesting potential avenues for future research in the Czech context.